2020
DOI: 10.1038/s41467-020-15894-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to UV radiance predicts repeated evolution of concealed black skin in birds

Abstract: Plumage is among the most well-studied components of integumentary colouration. However, plumage conceals most skin in birds, and as a result the presence, evolution and function of skin colour remains unexplored. Here we show, using a database of 2259 species encompassing >99% of bird genera, that melanin-rich, black skin is found in a small but sizeable percentage (~5%) of birds, and that it evolved over 100 times. The spatial distribution of black skin follows Gloger's rule, which states that pigmentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 55 publications
(57 reference statements)
1
41
1
Order By: Relevance
“…However, for brighter feathers maximum skin temperatures were higher than maximum surface temperatures, likely due to deeper light penetration into the plumage [4], backscattering effects [63] and greater transmittance [19]. Interestingly, some sunbird species have black skin, which not only protects them against high ultraviolet irradiation [64] but can further lead to higher heat loads at skin level and more so under higher light transmitting and heat insulating tissues (e.g. as in polar bears [65]).…”
Section: Discussionmentioning
confidence: 99%
“…However, for brighter feathers maximum skin temperatures were higher than maximum surface temperatures, likely due to deeper light penetration into the plumage [4], backscattering effects [63] and greater transmittance [19]. Interestingly, some sunbird species have black skin, which not only protects them against high ultraviolet irradiation [64] but can further lead to higher heat loads at skin level and more so under higher light transmitting and heat insulating tissues (e.g. as in polar bears [65]).…”
Section: Discussionmentioning
confidence: 99%
“…Populations of plants and animals can also genetically adapt to tolerate high UV irradiances. These adaptations are evident in increases in melanin pigment of bird skin with decreasing latitudes [ 164 ], and latitudinal changes in flavonoids of crop plants such as broad bean ( Vicia faba ). In this latter example, a field experiment using UV filters showed that the flavonoid profile of a cultivar native to high elevations in Ecuador and Columbia differed from that of a cultivar from Sweden at low elevation [ 165 ].…”
Section: Terrestrial Ecosystems and Biodiversitymentioning
confidence: 99%
“…[ 57 ] A very recent study has shown that birds with melanin‐enriched skin live in high radiation regions (closer to equator) and tend to be bald and/or have white feathers, suggesting their black skin is critical for protecting them from UV radiation. [ 58 ]…”
Section: Optical Functions In Naturementioning
confidence: 99%